Adaptive reuse of industrial heritage in a polycentric metropolitan area: the case of GZM (Silesian Province, Poland) - Koj, Jacek (Bulletin of Geography. Socio-economic Series, 2024)
The article discusses the process of converting industrial heritage for new uses in a large Central European metropolitan area (the case of GZM: Górnośląsko-Zagłębiowska Metropolia – Metropolis GZM). The aim of the research is to investigate the distribution of industrial heritage sites and to identify the factors influencing their current use. The methods include desk research (analysis of documents and database queries), field research and spatial analysis. The research has found 119 preserved industrial heritage sites, whose distribution reflects the historical spatial pattern of industrialisation and the priorities of the restructuring policy. To date, 70 sites have been converted, with commercial and institutional uses dominating and residential and recreational uses being much less common. Although minor differences in the average distance of industrial heritage sites from the city centre, shopping centre, university, train station or motorway exit depending on their current use have been observed, they were not statistically significant.